Terminação de cordeiros confinados com silagem de sorgo, resíduo úmido de cervejaria ou bagaço de uva como volumoso da dieta - Simões, Robson Rodrigues (2020)
The experiment has evaluated a total of thirty non castrated weaned lambs at 55 days of age from Texel x Ile de France breed cross and were equally randomly distributed in treatments: Sorghum (SS) silage + concentrate, wet brewer grains (WBG) silage + concentrate and grape pomace (GP) silage + concentrate for lambs kept on feedlot to evaluate nutrients intake, apparent digestibility and nitrogen balance, carcass and non-carcass components and intake behavior. Diets were isoproteic containing 18.81% and same acid detergent fiber from forage with 28%. Concentrate diets were composed by corn, soybean bran, and calitic limestone. Lambs were to slaughter when reached target of 36 kg of live weight. There were no diffetences (P>0,05) between WBG and GP treatments for intake of dry matter (DM), organic matter (OM), crude protein (CP) and ether extract (EE) in (kg/day) greater (P≤0,05) than lambs from SS treatment. Intake of DM, EE and total digestibility nutrientes (TDN) in (%, live weight) were greater (P≤0,05) for WBG and GP, however for acid detergente fiber (ADF) was greater (P≤0,05) from WBG than SS. DM (g/kgPV0,75) was greater (P≤0,05) for GP than SS, however for OM, EE and TDN were greater (P≤0,05) for WBG and GP than SS. Daily weight gain (DWG) was greater (P≤0,05) in GP which has presented better (P≤0,05) food conversion (FC). Dry matter digestibility (DMD), crude protein digestibility (CPD) and acid detergente fiber digestibility (ADFD) were greater (P≤0,05) for GP than SS. Total nitrogen retained (TNR) (%) was greater (P≤0,05) for WBG. Hot and cold carcass yield, carcass compactness index (CCI, kg/cm), liver and renal fat proportion were better (P<0,05) for WBG and GP than SS. Heart proportion was greater (P≤0,05) for GP than SS. Skin and kidneys proportion were greater (P≤0,05) for GP than SS and WBG. Full and empty rumen (%) were greater (P≤0,05) for SS. Full and empty small intestine (%) were greater (P≤0,05) for GP than WBG. Total gastrointestinal tract content (TGTC) was greater (P≤0,05) for SS. Rumination time (RUT), total chewing time (TCT), water intake (WATER) by (min/day and %) were greater (P≤0,05) for lambs from GP treatment. Meal activity (min/ MEAL) was better (P≤0,05) for WBG and GP treatment. This was followed by a greater (P≤0,05) intake of DAM, chewing efficiency (CHEF) of DAM and NDF, rumination efficiency (REF) of NDF for WBG and GP treatment, whereas for DWG and REF of DAM was better (P≤0,05) for GP. In conclusion, use of WBG and GP in certain dry matter proportion in diet for lambs in feedlot improve the nutrients intake by better chewing efficiency and rumination of DM and NDF. WBG and GP improve hot and cold carcass yield and compactness index. GP increase DWG and FC. WBG provides better use of dietary protein generating greater retention of body nitrogen.